(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay analyses the issue of the status of the child born through surrogacy and the possible instruments for establishing the bond with the intended parent. After an examination of the regulating principles of the phenomenon, the essay focuses on the solutions proposed by Italian jurisprudence, which has recently reaffirmed that adoption simple constitutes the only way for establishing the parental relationship with the child born through surrogacy. The essay provides some critical insights into the approach that places the dignity of women and the interest of the child in antinomy with each other, suggesting the opportunity to distinguish the instruments to discourage surrogacy from those to protect the continuity of status.